Tadresi mawnat Resource pack Nursery term 1 (Lahore: The City School)
Oral language development through greetings, basic phrases, and songs. Introduction to selected Urdu alphabets (e.g., ). Recognition of the sound and shape of letters through visuals and repetition. Vocabulary building through themes (e.g., fruits, animals, body parts, family). Listening comprehension through stories and simple instructions.
Play-based and experiential learning with visual and auditory reinforcement
Shelving location: M4
Children are in the per-literacy stage, just beginning to explore language through listening, speaking, and observing. They respond well to repetition, rhythm, storytelling, and visuals. Most are still developing their oral vocabulary in Urdu (especially in multilingual contexts). They learn through play, songs, stories, and social interaction.
Keywords: TCS Urdu Resource Pack; Urdu text book Term 1